MANAJEMEN PEMBELAJARAN SENTRA ALAM PADA ANAK USIA DINI DALAM MENINGKATKAN KECERDASAN KONGNITIF ANAK - Tamami, Nur; Aunullah, Indi Aunullah; Widat, Faizatul; Rani, Rosita Wahyu (Universitas Nurul Jadid, 2021)
This study aims to understand and analyze the management of natural center learning in early childhood in improving children's cognitive intelligence in Raudlatul Athfal Zainul Hasan, Tambelang Village, Krucil District, Probolinggo Regency. This research uses a qualitative type of case study. Data collection techniques are carried out through interviews, observation and documentation. The data analysis was carried out in a circular manner, starting from the data display, followed by drawing conclusions. The results showed that the learning management of natural centers in improving students' cognitive intelligence was carried out through planned and systematic planning by the teacher with reference to policies that have been determined by the government and existing local policies, followed by implementation of learning activities that try to bring students to the real world and ends with an evaluation based on authentic assessment.